VARIACION GEOGRAFICA EN EURYMETOPUM EBURNEOCINCTUM (SPINOLA, 1849) (COLEOPTERA: CLERIDAE), DESCRIPCION DE SUBESPECIES Y CONSIDERACIONES BIOGEOGRAFICAS - Solervicens A., Jaime (Acta Entomológica Chilena, 2022)
The morphologic and chromatic variations in populations of Eurymetopum eburneocinctum (Spinola, 1849) (Coleóptera: Clcridae) is discussed in this paper in 789 samples from Chilcan localities dislribuled bclwcen 31°33’ and 46°16’ Latitude South. The morphologic analysis considered the last abdominal scgmenls and genital characters of 77 males and 58 females; the morphometric evaluation was made on information gathered from 30 males and 30 females, considering head width, pronotum width, humeral width, length of pronotum and length of clitra, bcsides total length of individuáis. The statistical trcatmenl included variance analysis and discriminan! analysis. Chromatic variations werc performcd through 44 differenl characters in the total samplc, trying lo evalúate color frequency and estimaling similarity among populations. Four new subspecies are described, i.e., E.e. eburneocinctum, E.e. quinteroensis, E.e. quereoensis, and E.e. elbatoensis, and a biogeographic interpretation of these variations is further proposed.